(untitled) (Colombia Medica, 2012)
The determination of the values of central venous pressure has long been used as a guideline for volumetric therapy in the resuscitation of the critical patient, but the performance of such parameter is currently being questioned as an effective measurement of cardiac preload. This has aroused great interest in the search for more accurate parameters to determine cardiac preload and a patient’s blood volume. Goals and Methodology: Based on literature currently available, we aim to discuss the performance of central venous pressure as an effective parameter to determine cardiac preload. Results and Conclusion: Estimating variables such as end-diastolic ventricular area and global end-diastolic volume have a better performance than central venous pressure in determining cardiac preload. Despite the best performance of these devices, central venous pressure is still considered in our setting as the most practical and most commonly available way to assess the patient’s preload. Only dynamic variables such as pulse pressure change are superior in determining an individual’s blood volume.